Manajemen Keamanan Data Dalam Era Tansformasi Digital Dan Cloud Computing - Pandu, Rafie Mahesa; Muttaqin, Hudan Aghil; Dias, Dias Satrio Ajie Widodo (Journal of Informatic and Information Security, 2024)
Digital transformation has driven the use of cloud computing technology in various sectors, including business and entertainment. However, the implementation of this technology poses significant data security challenges. This study aims to analyze the application of cloud computing technology in digital platforms such as Instagram, WhatsApp, TikTok, Netflix, and Spotify, as well as the security challenges faced. Using a qualitative descriptive approach, the study identifies security strategies used to protect user data, including encryption, access management, and real-time monitoring. The findings reveal that collaboration between cloud service providers and users is key to addressing security threats in the era of digital transformation.